Taxonomic and phylogenetic contributions to Diatrypaceae from southeastern Tibet in China - Ma, Hai-Xia; Yang, Zhan-En; Song, Zi-Kun; Qu, Zhi; Li, Yu; Zhu, An-Hong (Frontiers in Microbiology, 2023)
In this study, we investigated the diversity of diatrypaceous fungi from southeastern Tibet in China. The phylogenetic analyses were carried out based on ITS and β-tubulin sequences of 75 taxa of Diatrypaceae from around the world. Based on a combination of morphological features and molecular evidence, a new genus - Alloeutypa, three new species - A. milinensis, Diatrype linzhiensis, and Eutypella motuoensis, a new combination - A. flavovirens, were revealed by the materials in China. Alloeutypa is characterized by stromatal interior olivaceous buff, stromata producing well-developed discrete, and ascospores allantoid, subhyaline. These characters separate the new genus from the similar genus Eutypa. Comprehensive morphological descriptions, illustrations and a phylogenetic tree to show the placement of new taxa are provided. All novelties described herein are morphologically illustrated and phylogeny investigated to better integrate taxa into higher taxonomic framework and infer their phylogenetic relationships as well as establish new genus and species. Our results indicate that the diatrypaceous fungi harbours higher species diversity in China.